THE IMPORTANCE OF THE ENGLISH IN ENGINEERING - Bozarov, F.; Mamatov, F. (ILIM hám JÁMIYET, 2025)
The article emphasizes the importance of English technical literature in aviation, including supporting students of higher military schools that train military pilots, students of other higher military schools that supply military personnel, pilots, engineers, and researchers to in-depth mastery of knowledge and understand technical manuals.